RESPON PARA PEMANGKU KEPENTINGAN BISNIS KELAPA SAWIT DI INDONESIA TERHADAP PEMBERLAKUAN RED OLEH UNI EROPA - , Rosita Dewi, Prof. Dr. M. Mohtar Mas'oed ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The implementation of Renewable Energy Directive (RED) by European Union has an impact not only for European Union member countries but also for non member countries. This directive is called mandatory target of a 20% share of renewable energies in the EU's energy mix by 2020 and at least 10% share of biofuels in transport by 2020. This regulation also set on sustainability criteria for biofuels that will used by European Union member countries. Indonesia as a biggest palm oil producer in the world concerns about the implementation of this legislation. The directive will impact the trade of the Indonesian palm oil to EU member countries. Furthermore, this condition shows many reactions from the stakeholder of Indonesian palm oil business. This research is qualitative research with descriptive analysis method. This research discusses about the impact of the implementation of EU renewable enrgy directive on sustainability of Indonesia palm oil development. This research also analyze about the response of the Indonesian palm oil stakeholder after the implementation of RED by EU and the strategy that taken by stakeholder after the implementation of RED by EU.